Sofosbuvir as a potential alternative to treat the SARS-CoV-2 epidemic - Rodrigo Jácome (Nature Portfolio, 2020)
Abstract As of today, there is no antiviral for the treatment of the SARS-CoV-2 infection, and the development of a vaccine might take several months or even years. The structural superposition of the hepatitis C virus polymerase bound to sofosbuvir, a nucleoside analog antiviral approved for hepatitis C virus infections, with the SARS-CoV polymerase shows that the residues that bind to the drug are present in the latter. Moreover, a multiple alignment of several SARS-CoV-2, SARS and MERS-related coronaviruses polymerases shows that these residues are conserved in all these viruses, opening the possibility to use sofosbuvir against these highly infectious pathogens.